PENGARUH MODEL PEMBELAJARAN TGT BERBANTUAN GAME MAKE A MATCH CARD TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 2 TANAH ABANG - Agustin, Nanda; Noviati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the TGT Learning Model assisted by the Make A Match Card game on student learning outcomes in the material of flora and fauna diversity in Indonesia at SD Negeri 2 Tanah Abang. The research method used is quasi-experimental with a Pretest-Posttest Control Group Design. The first sample consisted of 25 students for the experimental class using cooperative learning type TGT, and the second sample consisted of 22 students for the control class using cooperative learning without TGT. The research instrument used was a learning outcome test in the form of 20 multiple-choice questions. The analysis technique used in this study was the t-test. Based on the calculation results of the t-test, it was obtained that t-count = 0.422 and t-table = 0.05 with a significant level of 5%, which means t-count > t-table (0.422 > 0.05), so Ho is rejected and Ha is accepted. Therefore, it can be concluded that the cooperative learning type TGT assisted by the Make A Match Card game has an effect on student learning outcomes in the material of flora and fauna diversity in Indonesia.